Accounting Students' Understanding of the Importance of Information Technology Knowledge that Accountants Must Master in Running a Business in the Industrial Revolution Era (Empirical Study of Accounting Students at Muhammadiyah University of Sidoarjo): Pemahaman Mahasiswa Akuntansi Tentang Pentingnya Pengetahuan Teknologi Informasi Yang Harus Dikuasai Oleh Akuntan Dalam Menjalankan Usaha Di Era Revolusi Industri (Studi Empiris Mahasiswa Akuntansi Universitas Muhammadiyah Sidoarjo) - Solikhah, Sinta Faridatul; Hariyanto, Wiwit (Journal of Islamic and Muhammadiyah Studies, 2022)
This study aims to find out how accounting students understand the importance of information technology knowledge that accountants must master in running a business in the industrial revolution era, to find out how accounting students understand the importance of their ability to master information technology knowledge that must be mastered by an accountant and to find out the understanding of students who have a business about the knowledge of information technology that must be mastered by accountants to deal with the impact of the development of the current industrial revolution. In this study, researchers used qualitative methods. The informants in this. Study were students majoring in accounting for the 2018 and 2019 batches of Muhammadiyah University of Sidoarjo. Data collection techniques used are Interviews, observation and documentation. In this research, the triangulation used is source triangulation and technique triangulation. The results of this study indicate that there is no significant difference in the understanding of accounting students who have current businesses regarding the knowledge of information technology that must be mastered by an accountant in the current era of the industrial revolution. Knowledge of information technology is very important for accounting students who are having businesses. Because accounting is an activity that does not escape the role of technology in matters relating to financial data. An accountant will go hand in hand with information technology.